If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6u(5u+2)=-3u(3u-3)
We move all terms to the left:
6u(5u+2)-(-3u(3u-3))=0
We multiply parentheses
30u^2+12u-(-3u(3u-3))=0
We calculate terms in parentheses: -(-3u(3u-3)), so:We get rid of parentheses
-3u(3u-3)
We multiply parentheses
-9u^2+9u
Back to the equation:
-(-9u^2+9u)
30u^2+9u^2-9u+12u=0
We add all the numbers together, and all the variables
39u^2+3u=0
a = 39; b = 3; c = 0;
Δ = b2-4ac
Δ = 32-4·39·0
Δ = 9
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$u_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$u_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{9}=3$$u_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(3)-3}{2*39}=\frac{-6}{78} =-1/13 $$u_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(3)+3}{2*39}=\frac{0}{78} =0 $
| -3x^2+x=-8 | | m^2+20=-70 | | y.20-9=11 | | 3(4b-1)=-8(b-4)+5 | | 5/6(6a-6)+2=3/4(12a+4)+14 | | 12x+5.3=11x-5.8 | | 23y^2-252y-2016=0 | | -b+b^+6=0 | | 6x+28=-10 | | 8x+6=3x-12 | | 2x^2+80x+675=0 | | 10x+1/3x=140 | | 4+3x=12-15x | | 5x+2/3x=126 | | -5.6=x.20+12.2 | | 9x+1/5x=80 | | x.25+10=1 | | 5-5(x+5)-5x=9+1 | | 8x+19+4x+44+13x-3=360 | | -(-4x-6)=1/2(6x+2) | | 2x+6=3x+6+x | | 5-5(x-5x)=9+1 | | 5-5(+5)-5x=9+1 | | 8-5=3-(x+5) | | 2x-x+3=3-(-5) | | c(20,8)=5079110405 | | 2=6x-4x+8 | | 5x-6x+5=-3 | | c(25,10)=3268760 | | -40=5(8x+8) | | p(25,10)=1.186167629*10^13. | | 10x+45=-5 |